2016
DOI: 10.1093/ckj/sfw076
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of health literacy and medication adherence in adult kidney transplant recipients

Abstract: BackgroundThere is a high prevalence of non-adherence to immunosuppressants in kidney transplant recipients. Although limited health literacy is common in kidney recipients and is linked to adverse outcomes in other medical populations, its effect on medication adherence in kidney transplant recipients remains poorly understood. The objective was to investigate the effect of lower health literacy on immunosuppressant adherence.MethodsKidney recipients who were at least 6 months post-transplant and outpatients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
3
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 46 publications
1
59
3
10
Order By: Relevance
“…Most patients reported very high degrees of medical adherence, which is in contrast to the results of previous research on medical adherence in CKD patients (Loghman‐Adham 2003; Demian et al . 2016). However, when evaluating patients' medical prescription collection from the pharmacy, our findings were less encouraging and were following those of previous studies, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients reported very high degrees of medical adherence, which is in contrast to the results of previous research on medical adherence in CKD patients (Loghman‐Adham 2003; Demian et al . 2016). However, when evaluating patients' medical prescription collection from the pharmacy, our findings were less encouraging and were following those of previous studies, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, prior studies among kidney transplant recipients found that lower health literacy was associated with increased serum creatinine levels, an indicator of renal dysfunction. 7 , 17 In a recent systematic review of health outcomes and health literacy in chronic kidney disease patients (4,367 non-dialysis, 13,202 dialysis, 390 transplant, and 341 unspecified), low health literacy was associated with increased risk of mortality, emergency department use, and hospitalization. 14 A study of liver transplant recipients conducted by Serper et al noted that increased treatment knowledge, which was associated with better health literacy, resulted in a 15% reduction in posttransplant hospitalization (incidence rate ratio [IRR]=0.85, 95% CI=0.74–0.97).…”
Section: Posttransplant Outcomes Affected By Health Literacymentioning
confidence: 99%
“…Participants indicated that lack of knowledge and formal education as huge barrier to transplant management as Obi et al [5] confirmed. Similarly, a study done by Demian et al [26] indicated that worse adherence was associated with poorer overall health literacy. Inadequate health education was a strong barrier to self-management.…”
Section: Barriers To Self-managementmentioning
confidence: 87%